Assessing the environmental risk posed by a legacy tanker wreck: a case study of the RFA War Mehtar. (1st May 2022) - Hill, Polly G; Skelhorn, Matthew; Leather, Stuart
Abstract: The ocean floor is littered with thousands of wrecks containing hazardous fuels, lubes, armaments and cargoes that have polluted, are polluting, or will pollute the marine environment. The UK Ministry of Defence manages the environmental risk associated with its ∼5, 700 military wrecks through the Wreck Management Programme. This paper explores the methods used to assess the environmental risk associated with the wreck of the Royal Fleet Auxiliary (RFA) tanker RFA War Mehtar, which lies at approximately 39 m depth, 15 nm east of Great Yarmouth, United Kingdom. The methods employed include archival research, computational oil spill modelling combined with sensitivity mapping, environmental sampling and hydrocarbon concentration analysis, multibeam echosounder sonar surveys and neutron backscatter probe measurements. Each method is described, and its efficacy discussed. The archival research was essential to determine what fuel and cargo the RFA War Mehtar sank with; but only when high-resolution multibeam sonar images were combined with the ship's plans and neutron backscatter measurements from individual tanks could one confidently conclude that the wreck does not pose a significant pollution risk.